Development of Road Rules Learning Application Through Game-Based Approach - Liew, Win Jun; Md Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2021)
Road Signs Education is an application which is using the gamification approach to learn the traffic sign. To learn driving, the problem is we need an actual car and get a driving license at a proper driving school or institution by taking the course of Driver Education Curriculum (DEC). All these processes required a lot of cost and time, especially for those foreigners. Therefore, the project objectives are to design and develop a road sign learning application using a gamification approach on the Android platform and evaluate the user acceptance level of the application using the Technology Acceptance Model (TAM). Moreover, the main components that have been developed in Road Signs Education are including “Learn” mode, “Test” mode, and “Play” mode. Mobile Application Development Life Cycle is chosen as the methodology to develop the application. Furthermore, the application is developed by using Unity and C# programming language. Road Signs Education is finally developed completely, and it was tested using alpha testing and user acceptance testing. The results of the user acceptance test indicated a positive feedback rate of 88.01%. Overall, the developed application has achieved all the objectives of the project. Thus, this game-based application could act as a traffic sign learning tool for the community to have a better knowledge about the traffic sign in Malaysia.